THE AMERICAN DREAM IN TENNESSEE WILLIAMS’ THE GLASS MENAGERIE - Elizabeth Amalo , Radina Anggun N., Imam Dui Agusalim , Irwan Sumarsono , Eny Kusumawati, (JBT (JURNAL BISNIS dan TEKNOLOGI), 2024)
This study focused to analyze the American dream reflected in Tennessee Williams’s The Glass Menagerie through the dreams that each character in the play has. The analysis focused on what each character dreams for and how they tried to make their dream come true, whether they succeeded or failed in making their dream come true or not. The writers used the historical background and the concept of the American dream that holds three points, namely being a richer, better, and fuller life. The writers used the descriptive qualitative method in analyzing the study. The needed data were collected by doing library research. The main data were derived from the play itself and the supporting data are collected from several sources such as journals, e-books, and other sources downloaded or accessed from the internet. To analyze this topic, the writers traced the background of the play, when it was written by Williams, to find out the social and economic condition of the play. From the study that the writers conducted, it can be concluded that all the characters in the play have their own dream, but nobody succeeds to reach his or her dream.